Penerapan Teknik Self-Monitoring dan Positive Reinforcement dalam Meningkatkan Perilaku Assertif Pada Individu Korban Toxic Relationship - Miftahul Rahmah; Wahyu Windiastuti Rahmawati; Muhammad Jamaluddin (Indonesian Journal Publisher, 2025)
This study aims to examine the effectiveness of self-monitoring and positive reinforcement techniques in increasing assertive behavior in individuals who are victims of toxic relationships. This research uses a Single Subject Research (SSR) method with an ABAB design. The subject of this study was a 23-year-old woman who had been in a toxic relationship for 2 years. Data collection was carried out through direct observation, self-monitoring sheets, and behavioral assessment scales. The intervention was implemented for 8 weeks with measurement of assertive behavior frequency before, during, and after intervention. The results showed a significant increase in assertive behavior from the baseline phase (average 2.1 times per week) to the intervention phase (average 8.3 times per week). Visual analysis showed a stable and consistent upward trend. This study concludes that the combination of self-monitoring and positive reinforcement techniques is effective in increasing assertive behavior in victims of toxic relationships